Tax Digitalization, Final Tax Incentives, And Sanctions Toward MSME Tax Compliance: Tax Digitalization, Final Tax Incentives, and Sanctions: Their Impact on MSME Tax Compliance - Nindya Kartika Kusmayati; Yuli Kurniawati; Nunuk Latifah; Bayu Agus Permadi; Dini Febriani (Akademi Komunitas Negeri Putra Sang Fajar Blitar, 2026)
Backgrounds. This study aims to examine the impact of tax digitalization, final income tax incentives, and tax penalties on the tax compliance of small and medium enterprises (SMEs) in Lamongan Regency.Methods. The research subjects consist of small and medium enterprises (SMEs) in Lamongan Regency. Primary data were collected from 95 SME taxpayers using a structured questionnaire distributed online via Google Forms. The respondents were SME owners or managers who are registered as taxpayers and actively operate their businesses. The sampling technique applied in this study was purposive sampling, with respondents selected based on their relevance to the research objectives. This study employs a quantitative approach using a survey method. Data were analyzed using SPSS version 25.0 with multiple linear regression analysis.Results. The findings indicate that tax penalties have a positive effect on SME tax compliance. However, tax digitalization and final income tax incentives do not have a significant effect on compliance levels. Simultaneously, the three variables collectively influence SME tax complianceConclusions. The study concludes that although not all tax policy instruments individually have a significant impact, a comprehensive and well-designed tax policy framework remains essential for strengthening tax compliance among SMEs.